Sloshing in Medium Sized Tanks Under Earthquake Load - YAZICI, GÖKHAN (My University, 2015)
This paper presents results obtained by numerical study of sloshing effects in medium sized rectangular tanks subjected to a long-period seismic excitation. The Smoothed Particle Hydrodynamics (SPH) method is used, and the wave displacement and pressure are analysed. The intensity of sloshing effects depends not only on the peak ground acceleration but also on the dominant frequency of ground motion. Excessive sloshing displacements and pressures increase when the natural period of the contained liquid approaches the dominant period of ground excitation.
Keywords: Sloshing; Smoothed Particle Hydrodynamics; SPH Method; Free Surface Flow